Mobile Learning with Edmodo : Digital Virtual Class - Rini Sefriani; Rina Sepriana; Popi Radyuli; Arlina Yuza (Universitas Pendidikan Ganesha, 2023)
The problem found in the field was the limitation of face-to-face learning for students due to the outbreak of the Covid-19 pandemic. This study was conducted to analyze the feasibility, practicality and effectiveness of online learning using an android smartphone that utilizes the Edmodo learning management system in the Learning Evaluation course. This type of research is research and development. The development model used is the ADDIE Model, namely Analysis, Design Develop, Implementation and Evaluation. The instrument in this research is a test question. The sample in this study were students majoring in English Education. The data were analyzed using Microsoft Excel. The results showed that the level of validity of mobile learning with Edmodo was 84.75% with a valid interpretation used, practicality of 86.64% which means it is very practical to use and for the level of effectiveness using the N-gain test. The N-gain value of 0.7 means that the use of mobile learning with Edmodo is effective in learning evaluation lectures. It can be concluded that the use of mobile learning with Edmodo can optimize learning activities during the Covid-19 pandemic and can be an alternative for teachers and students in e-learning learning in the future.